Emergence: A Parameter of the Effectiveness of Artistic Creativity—A Study of Dance Improvisation - Randazzo, Alessandra Florentina (Cultural Arts Research and Development, 2026)
When discussing artistic improvisation, effectiveness is generally dismissed for at least two main reasons. On the one hand, an improviser cannot anticipate the appropriate means to achieve an end that, by definition, they do not set in advance—hence the inherent risk of failure. On the other hand, an improviser does not aim to showcase their virtuosity in appropriating a particular movement vocabulary, insofar as their intention is rather to circumvent habitual patterns and expand their vocabulary. The aim of this article, however, is to demonstrate that invoking the notion of effectiveness is not incompatible with the indeterminate nature of improvisation. In this context, our thesis is that emergence—implying a sudden appearance of novelty—can be seen as a key parameter in fostering the effectiveness of artistic creativity in an improvisation. We will focus our discussion on the case of dance improvisation, particularly as it has developed since the American postmodern period of the 1960s and 1970s. This thesis is elaborated through several lines of argument. It distinguishes between two forms of emergence: a framework for emergence, related to emergence as an occurrence, and an emerging framework, related to emergence as downward causation. It differentiates, consequently, two specific senses of effectiveness: the precision and openness of action guidelines, enabling the expansion of the dancer’s movement vocabulary, and the reduction of the field of possibilities through collectively made real-time decisions, which allow for the creation of new norms of action and generate a unified sense and form among dancers’ actions. This leads us finally toward a new approach to artistic creativity.